Effects of ZrB2 addition on texture development and properties of porous Si3N4-ZrB2 composites by magnetic field alignment. Issue 3 (3rd July 2019) - Yang, Zhigang; Zhao, Zhijia; Wang, Hao; Song, Huaqi; Yu, Jianbo; Ren, Zhongming; Ren, Shuxia; Ma, Shiqing; Wang, Zhi
ABSTRACT: Textured porous Si3 N4 -ZrB2 composites were prepared by the gel-casting method assisted by magnetic field alignment technology and subsequent pressureless sintering. These results showed that when a 6 T magnetic field was applied, the ZrB2 grains also formed a c-axis orientation in the textured green bodies, except for β-Si3 N4 grains, which formed an a- or b-axis orientation. The increasing ZrB2 content inhibited the degree of texture of the Si3 N4 and ZrB2 grains in the green bodies, respectively. After sintering at 1800 °C, new ZrN and BN phases without grain orientation characteristics formed by the reaction between Si3 N4, ZrB2 and N2 and the ZrB2 phase disappeared completely. The sintering process promoted the degree of texture of Si3 N4 as the matrix increases. Meanwhile, the variations in the degree of texture of Si3 N4 with changes in the ZrB2 content were consistent with that in the green body. Additionally, when 10 wt% ZrB2 content was introduced, the apparent porosity reached its highest value and the bulk-density reached its lowest value, leading to the appearance of least strength. In textured porous composites, the strength was mainly affected by the densification process instead of the grain orientation. Also, no evident difference in strength existed between the two directions owing to the function of high porosity.